Financial Sector Strategies and Financial Sector Outcomes : Do the Strategies Perform? - Melecky, Martin; Podpiera, Anca Maria (World Bank, Washington, DC, 2018)
Financial sector strategies enable financial policy makers and stakeholders to take a holistic view of the financial development needs in their country and formulate balanced financial policies. They help policy makers consider the systemic risk that different development policies involve and choose an informed way forward. This study constructed a new data set of historical financial sector strategies covering 150 countries over 1985-2014. It assesses the strategies using the rating criteria proposed by Maimbo and Melecky (2014). It further investigates how the quality of the strategies can affect financial sector outcomes, such as financial depth, inclusion, efficiency, and stability. The investigation finds that the use of financial sector strategies helped increase financial sector deepening, inclusion, and stability, and this impact could be greater for higher-quality strategies. However, a significant relationship between the use of strategies and the efficiency of banks is not confirmed. One way how financial sector strategies can improve financial sector outcomes is by improving the regulatory framework for finance.